Nanotechnologies for the detection and treatment of endometriosis - Sahni, Maneesha; Day, Emily S. (Frontiers in Biomaterials Science, 2023)
Endometriosis is an incurable gynecologic disease characterized by endometrial-like tissue growth outside of the uterine cavity. It affects approximately 10% of reproductive age women, who endure pelvic pain during periods and/or sexual intercourse and who suffer from reduced fertility and diminished quality of life due to the side effects of current treatments. To improve the management and prognosis of endometriosis patients, researchers have recently begun to develop nanoparticlebased diagnostics and treatments that are more effective and less invasive than existing approaches. This review discusses the current state of the field and highlights considerations for the continued development of nanotechnologies for the diagnosis and treatment of endometriosis.